Bronchopleural fistula closure with vascular plug and intrapleural glue administration - Neeraj Sharma; Vasu Vardhan; Chandan Singh Katoch; Aseem Yadav (Indian Journal of Respiratory Care, 2020)
The presence of communication between a mainstem, lobar, or segmental bronchus and the pleural place is called a bronchopleural fistula (BPF). It is commonly caused as a result of postoperative complication of lung resection surgeries, chemotherapy or radiotherapy for lung cancer, persistent spontaneous pneumothorax, empyema, lung abscess, and tuberculosis. A 20-year-old male underwent decortication for diffuse right-sided tuberculous pleural thickening. Postsurgery, he developed BPF. He underwent open thoracic surgery for BPF closure. However, he continued to have air leak and persistent empyema. Repeat evaluation revealed a large BPF at the anterior segment of the right upper lobe on computed tomography chest, which was confirmed on bronchoscopy. He underwent bronchoscopic closure (under fluoroscopic guidance) of BPF with a 6 mm × 7 mm vascular plug successfully. Major air leak stopped and lung expansion increased on chest X-ray. However, small air leaks (alveolar-pleural fistula) persisted. Later, he was subjected to intrapleural diluted fibrin glue administration (fibrinogen + aprotinin + thrombin) via a chest tube at bedside. Application of diluted fibrin glue through the chest tube succeeded in completely sealing the small air leaks. Radiologically, there was no further lung collapse and the pleural space was nearly obliterated.